Drug utilization and teratogenicity risk categories during pregnancy - (:unkn) unknown (HEALTH COMMUNICATIONS INC, 2007)
A limited number of studies have investigated in detail the use of drugs during pregnancy. Researchers in the present study investigated the details of drug utilization in pregnant women during the month before pregnancy, at the time that they became aware of the pregnancy, and during the first trimester. Face-to-face interviews were conducted with 359 pregnant women who were admitted to the fetal medicine unit at a university hospital for diagnosis and follow-up. A questionnaire was used to document sociodemographic characteristics and details of drug use. Drugs were categorized according to the US Food and Drug Administration fetal risk classification. Mean maternal age was 29.9 +/- 5.1 y, and mean gestational age was 1 9.6 +/- 9.5 wk. Many of the pregnant women studied (46.6%) were university graduates, and most (61.9%) had a relatively high annual income. Mean gestational age when participants first learned of their pregnancy was 39.8 +/- 1 6.4 d. One hundred seventeen participants (32.6%) used drugs during the month before conception, 54 (15%) at the time when they learned of their pregnancy, 180 (50.1%) at the time of the interview, and 289 (80.5%) during the first trimester. The percentages of drugs in categories D and X used by these subjects were 14%, 13.5%, 2.9%, and 5.9%, respectively. Most of the drugs were hormones. The total rate of drug utilization was not high before and during the first trimester of pregnancy. A considerable number of women were using drugs from the D and X categories; however, these numbers decreased significantly when women learned of their pregnancies. intake of folic acid, vitamins, and iron was very low during the preconception period and was not high enough during the first trimester; this suggests that particular attention should be paid to the use of beneficial safe drugs during the preconception and early pregnancy periods.
Keywords: pregnancy; drug utilization; teratogenicity; preconception care; LACTATION; WOMEN; MEDICATION; THERAPY